Gelidium gonzalezii sp. nov. (Gelidiales, Rhodophyta) from the Mexican tropical Pacific based on molecular and morphological evidence - Quiroz González, Nataly (2020)
There are currently 23 reported species of Gelidium in Mexican Pacific coastal waters. Many of these species require taxonomic verification. Gelidium sclerophyllum is a species reported from the northern Gulf of California to the tropical region of the Mexican Pacific, but there is large morphological variation among populations. The objective of this research was to evaluate this species using a morphological and molecular approach, with COI-5P and rbcL molecular markers. A total of 13 samples were collected from five sites in the Mexican Tropical Pacific. Phylogenetic analyses resolved these specimens within a separate clade from that which includes the type of G. sclerophyllum and other Central American specimens. Differences with other species are subtle and based mainly on size, branching pattern, shape of tetrasporangia sori and size of tetraspores. The sequence divergences and the subtle morphological differences between these two clades support their recognition as two distinct species, and Gelidiumgonzalezii sp. nov. is proposed for specimens from the Mexican Tropical Pacific.